Test–Retest Reliability of Measures Commonly Used to Measure Striatal Dysfunction across Multiple Testing Sessions: A Longitudinal Study - Palmer, Clare E.; Langbehn, Douglas; Tabrizi, Sarah J.; Papoutsi, Marina (Frontiers in Psychology, 2018)
Cognitive impairment is common amongst many neurodegenerative movement disorders such as Huntington’s disease and Parkinson’s disease across multiple domains. There are many tasks available to assess different aspects of this dysfunction however it is imperative that these show high test-retest reliability if they are to be used to track disease progression or response to treatment in patient populations. Moreover, in order to ensure effects of practice across testing sessions are not misconstrued as clinical improvement in clinical trials, tasks which are particularly vulnerable to practice effects need to be highlighted. In this study we evaluated test-retest reliability in mean performance across three testing sessions of four tasks that are commonly used to measure cognitive dysfunction associated with striatal impairment: a combined Simon Stop-signal Task; a modified emotion recognition task; a circle tracing task; and the trail making task. Practice effects were seen between sessions 1 and 2 across all tasks for the majority of dependent variables, particularly reaction time variables; some, but not all, diminished in the third session. Good test-retest reliability across all sessions was seen for the emotion recognition, circle tracing, and trail making test. The Simon interference effect and stop-signal reaction time (SSRT) from the combined-Simon-Stop-Signal task showed moderate test-retest reliability however, the combined SSRT interference effect showed poor test-retest reliability. Our results emphasize the need to use control groups when tracking clinical progression or use pre-baseline training on tasks susceptible to practice effects.